Types and abundance of phytoplankton in the Samsam Peat Swamp, Kandis Sub-District, Siak District, Riau Province - Zurkartika '; Madju Siagian; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Samsam swamp is located in the peat swamp area and flooded during rainy season. To understand the types and abundance of phytoplankton present in that swamp, a study has been conducted in March 2016. There were four sampling sites, namely S1 is in the upstream (almost no human activity); S2 ( around palm plantation); S3 (around the newly planted palm plantation) and S4 (far from palm plantation). Water sampler were taken once/week for 3 week period. Results shown that there are 21 species of phytoplankton present in the swamp. They were classified into three classes, `namely: Bacillariophyceae (12 species), Chloropyhceae (6 species) and Cyanophyceae (3 species). The average of phytoplankton abundance was around 2,804 – 4,135 cells/L. While the water quality parameters were as follows: temperature: 30 - 320C, transparency: 30 - 40 cm, depth: 83 - 114 cm, pH: 4 - 5, CO2: 8.66 - 9.32 mg/L, DO: 3.96 - 4.65mg/L, nitrate: 0.45 - 0.58 mg/L and phosphate: 0.36 - 0.56 mg/L. Based on the abundance of pyhtoplankton, it can be concluded that the Samsam peat swamp water can be categorized as oligotrophic.Keyword : Phytoplankton, Samsam Peat Swamp, Water Quality and Oligotrophic